2023
DOI: 10.22235/cp.v17i1.3051
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas e invariancia de medida de una escala de autoeficacia académica en estudiantes universitarios de cinco países latinoamericanos

Abstract: El objetivo fue analizar la invarianza de medición de la Escala de Autoeficacia Percibida Específica para Situaciones Académicas (EAPESA) entre estudiantes universitarios peruanos, mexicanos, colombianos, argentinos y brasileños, y su relación con el agotamiento emocional académico (AEA). Además de la EAPESA, se usó la Escala de Cansancio Emocional (ECE). Participaron 2142 estudiantes universitarios (70.26 % mujeres) entre los 16 y 35 años (M = 21.79). La estructura unidimensional de la EAPESA se corroboró en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In Peru, self-efficacy has been recently studied from a preferably psychometric perspective, through the analysis of various scales that measure teaching self-efficacy (Burga, 2015), academic self-efficacy (Alegre, 2014;Dominguez-Lara, 2014;Dominguez-Lara et al, 2012, Domiguez-Lara & Fernández-Arata, 2019, research self-efficacy (Dominguez-Lara, 2017), and self-efficacy in general (Alegre, 2013;. These investigations, however, have been based in the vast majority of cases on samples of university students in the city of Lima (capital of Peru), and have used models derived from Classical Test Theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Peru, self-efficacy has been recently studied from a preferably psychometric perspective, through the analysis of various scales that measure teaching self-efficacy (Burga, 2015), academic self-efficacy (Alegre, 2014;Dominguez-Lara, 2014;Dominguez-Lara et al, 2012, Domiguez-Lara & Fernández-Arata, 2019, research self-efficacy (Dominguez-Lara, 2017), and self-efficacy in general (Alegre, 2013;. These investigations, however, have been based in the vast majority of cases on samples of university students in the city of Lima (capital of Peru), and have used models derived from Classical Test Theory.…”
Section: Discussionmentioning
confidence: 99%
“…Dominguez-Lara (2017) for example, constructed a self-efficacy scale for research. The same author has also reported the psychometric properties of Palenzuela's Academic Situations Specific Perceived Self-Efficacy Scale (EAPESA) (Dominguez-Lara, 2014;Dominguez-Lara et al, 2012). In a recent study with this scale, evidence has been found that supports the convergence of the scores with those of the Brief Scale Study Satisfaction, while data was also obtained on the divergence between the EAPESA score and psychological distress (Carranza et al, 2022).…”
Section: Psychological Thoughtmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the most widely used instruments for measuring selfefficacy in the Peruvian context is the Scale of Perceived Self-efficacy Specific to Academic Situations (Escala de Autoeficacia Percibida Específica de Situaciones Académicas [EAPESA]; Palenzuela, 1983), in its version adapted to the Peruvian university environment (Dominguez-Lara, 2014). This instrument has been widely used because it is a brief and one-dimensional tool to measure academic self-efficacy, and its psychometric properties in different contexts have been showed to be adequate by previous studies (García-Fernández et al, 2010;Dominguez-Lara, 2014;Dominguez-Lara et al, 2023). Therefore, considering that research on the measurement of teacher self-efficacy in the Peruvian university context is limited, the purpose of this study is to develop and validate the Specific Perceived Selfefficacy Scale for Teaching (Escala de Autoeficacia Percibida Específica para la Docencia [EAPED]) in Peruvian university professors, based on the adaptation of the EAPESA items, incorporating a general domain, recent advances in the measurement of teacher self-efficacy and current methodological recommendations for exploring the factorial structure of the instruments.…”
Section: This Studymentioning
confidence: 99%
“…Las diferentes definiciones sobre autoeficacia académica que devienen del concepto de autoeficacia global de Bandura, el que según Domínguez et. al.…”
Section: Introductionunclassified